0.4 THz Broadband Terahertz Noise Source Based on Photoconductive Antennas - Yinwei Chen; Feifei Qin; Lijuan Liu; Zeyu Zhao; Pu Li; Yuehui Sun; Wenjie Liu; Yuncai Wang (Photonics)
Terahertz noise sources have important application prospects in noise figure measurements. In this paper, a 0.4 THz broadband terahertz noise source based on a photoconductive antenna is proposed. As a demonstration of feasibility, this terahertz noise source is generated by mixing three beams of Gaussian-shaped incoherent light. The resulting excess noise ratio (ENR) across different frequency bands is as follows: 20.9 dB, with a flatness of ±7.9 dB in the 75~110 GHz range; 19.3 dB, with a flatness of ±6.2 dB in the 110~170 GHz range; 20.6 dB, with a flatness of ±4.8 dB in the 170~260 GHz range; and 18.7 dB, with a flatness of ±4.3 dB in the 260~400 GHz range. These results demonstrate that the terahertz noise source based on photoconductive antennas that we proposed shows great potential in high-frequency bands and noise figure measurements.